Pemanfaatan Buah Timun dan Tanaman TOGA (Jahe dan Kayu manis) sebagai Sumber Infused Water - Romadhan, Siddik; Fajarianingtyas, Dyah Ayu; Puniman, Ach (Jurnal SOLMA, 2026)
Background: A healthy lifestyle for all ages needs to be instilled from an early age so that individuals have a caring attitude towards health. The tendency of elementary school students to consume packaged drinks in their daily lives. The purpose of implementing this community service activity is to improve students' knowledge and skills by training them to make cucumber and TOGA (ginger and cinnamon) Infused Water, as a concrete manifestation of sustainable education in support of the SDGs program. Method: This activity is implemented as community education and training on making Infused Water. Results: The results of this activity show that, in terms of student knowledge, there is a 90% increase (very high category), and that of student skills, a 47% increase (effective category). This activity concludes that educational activities involving the preparation of cucumber and TOGA-Infused Water can improve students' knowledge and skills at the elementary school level. Continuing education through Infused Water teaches students a healthy lifestyle. Conclusion: Students of SDN Kalianget Timur X responded positively to the educational activities on making cucumber-and-toga-infused water, which increased their knowledge and skills in maintaining their health by consuming healthy drinks.